Method of priming plants against abiotic stress factors and promoting growth - (:unkn) unknown (World Intellectual Property Organization, 2015)
A method of reducing cellular damage to a plant by treating the plant with a compound containing an NO-releasing moiety and an H2S -releasing moiety covalently bonded to an aspirin derived core or a NOSH compound is claimed. The compounds may also be used in a method of priming a plant against abiotic stress factors and a method of promoting plant growth.
Keywords: C07D339/04; Cellular damage; Plant